BIOACCUMULATION AND DISTRIBUTION OF Pb, Cu AND Fe IN WATER CHESTNUT (TRAPA NATANS VAR. BISPINOSA ROXB.) IN THE LUCKNOW REGION - MUKESH BABU,; DEEPA H. DWIVEDI, (The Bioscan, 2012)
Water bodies are primarily contaminated with heavy metals due to increasing urbanization, intensive practices of agricultural and industrial developments, etc. Heavy metals have been reported to be highly toxic to human health since they are not easily disintegrated and decomposed and can be bioaccumulated along the food chain. Therefore, heavy metal contamination in aquatic ecosystems, such as those being used for the cultivation of edible aquatic plants like water cress, trapa etc., is of primary concern. The present study was initiated to study the bioaccumulation of Pb, Cu and Fe by Trapa natans var. bispinosa Roxb. growing water bodies in Lucknow. The results indicate that the heavy metals accumulate in order viz., Pb: Leaf > root > peel> stem > kernel; Cu: root > leaf > stem > peel > kernel and Fe: root > stem > leaf > peel > kernel. The edible parts of Trapa natans accumulated metals from their surrounding water significantly. The metal accumulation potential of the plant parts varied considerably depending upon level of metal contamination in the water body in which the plants were growing.